2014
DOI: 10.7287/peerj.preprints.476
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differences in healthcare expenditures for inflammatory bowel disease by insurance status, income, and clinical care setting

Abstract: View the peer-reviewed version (peerj.com/articles/587), which is the preferred citable publication unless you specifically need to cite this preprint.Park MD, Bhattacharya J, Park K. 2014. Differences in healthcare expenditures for inflammatory bowel disease by insurance status, income, and clinical care setting. PeerJ 2:e587 https://doi.org/10.7717/peerj.587Di ff e r e n c e s i n h e a l t h c a r e e x p e n d i t u r e s f o r i n fl a mma t o r y b o we l d i s e a s e b y i n s u r a n c e s t a t u s ,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…4 Overall cost of IBD care is lower when it is mostly conducted in an outpatient setting. 15 A separate study had shown that the utilisation of IBD inpatient services was greater in disadvantaged communities, where access to expert outpatient care was unavailable for geographic or economic reasons. 16 In other words, in areas where multidisciplinary outpatient IBD services are available, the need for inpatient services has been superseded for patients with more severe disease and is preferable because it is cheaper, more convenient and efficient.…”
Section: Discussionmentioning
confidence: 99%
“…4 Overall cost of IBD care is lower when it is mostly conducted in an outpatient setting. 15 A separate study had shown that the utilisation of IBD inpatient services was greater in disadvantaged communities, where access to expert outpatient care was unavailable for geographic or economic reasons. 16 In other words, in areas where multidisciplinary outpatient IBD services are available, the need for inpatient services has been superseded for patients with more severe disease and is preferable because it is cheaper, more convenient and efficient.…”
Section: Discussionmentioning
confidence: 99%
“…These issues are especially pertinent as health systems begin to assume financial risk for all aspects of care for groups of patients. 110,111 Financial, resource, and access to care (especially emergency and urgent care) issues related to mental health screening were addressed above. However, there are broader financial barriers related to IBD care that need to be understood and addressed so that psychosocial domains can be included.…”
Section: Health System Barriersmentioning
confidence: 99%
“…Within the adult GI population, Park et al noted that non-Caucasian, higher poverty-level and underinsured patients were more likely to use inpatient care for services and treatment of inflammatory bowel disease as compared with counterparts with similar disease processes. 3 The literature regarding how health disparities affect the utilization of pediatric gastroenterology resources and procedures is limited. A recent study from our institution identified various factors associated with higher use of emergent GI procedures, including age < 5 and > 18 years, African American, or non-Caucasian race, male gender, Medicaid insurance, and Spanish-speaking language.…”
Section: Introductionmentioning
confidence: 99%